Factors Facilitating Early Emotion Understanding Development: Contributions to Individual Differences - Ogren, Marissa (Hum Dev, 2020)
Children’s emotion understanding is crucial for healthy social and academic development. The behaviors influenced by emotion understanding in childhood have received much attention, but less focus has been placed on factors that may predict individual differences in emotion understanding, the principle issue addressed in the current review. A more thorough understanding of the developmental underpinnings of this skill may allow for better prediction of emotion understanding, and for interventions to improve emotion understanding early in development. Here, we present theoretical arguments for the substantial roles of three aspects of children’s environments in development of emotion understanding: family expressiveness, discussions about emotions, and language development, and we discuss how these are interrelated. Ultimately, this may aid in predicting the effects of environmental influences on development of emotion understanding more broadly, and the mechanisms by which they do so.